Defect engineering in metal–organic framework nanocrystals: implications for mechanical properties and performance - Möslein, AF; Donà, L; Civalleri, B; Tan, J-C (American Chemical Society, 2022)
The growth process of metal–organic framework (MOF) nanocrystals defines their properties and functions. However, defects may be prevalent during the crystallization of even seemingly perfect MOFs, such as zeolitic imidazolate framework-8 (ZIF-8), and yet direct probing of such structural defects has been challenging because of the lack of nanoscale techniques to locally examine individual nanocrystals. Here, we directly study local defects, such as missing linkers or metal vacancies, in ZIF-8 nano- and microcrystals with near-field IR nanospectroscopy combined with density functional theory calculations. We track the chemical changes during crystallization and show that structural defects like zinc cations that are bound to molecules of the reactant gradually disappear with ripening of the crystals, while dangling and missing linker defects prevail. The resulting defect-terminating groups or open-metal sites produce mechanical anisotropy and reduce the Young’s modulus, as measured via tip force microscopy with nanoscale resolution and supported by theoretical modeling. However, these structural defects also open the door for defect engineering to tune the performance of ZIF-8 by offering additional adsorption sites for targeted catalytic reactions, chemical sensing, or gas capture.